Preparation method and application of copper-based electrocatalyst for electrocatalysis of carbon dioxide reduction reaction
By designing copper-5-mercapto-1-methyltetrazole nanostructure monomers to form copper-based metal-organic framework electrocatalysts, the selectivity problem of single-carbon product generation in carbon dioxide reduction reaction of copper-based electrocatalysts was solved, achieving efficient generation of multi-carbon products and improving catalyst stability.
Patent Information
- Application Number
- CN202510095646.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-31
- Filing Date
- 2025-01-20
- Publication Date
- 2025-12-02
AI Technical Summary
Existing copper-based electrocatalysts exhibit high selectivity for generating single-carbon products in the electrocatalytic reduction of carbon dioxide, but struggle to generate multi-carbon products. Furthermore, the catalysts suffer from insufficient stability and activity, leading to complex product formation and low Faraday efficiency.
A copper-based metal-organic framework electrocatalyst with an orthogonal three-dimensional interconnected structure composed of copper-5-mercapto-1-methyltetrazole nanostructure monomers forms an unsaturated Cu-1S-2N coordination structure by replacing Cu-O or Cu-N bonds with Cu-S bonds, providing closely spaced double copper sites to promote the CC coupling reaction.
At a potential of -1.15V, the copper-based electrocatalyst achieves a Faradaic efficiency of 70-75% for multi-carbon products and 50-55% for ethylene products, significantly improving the selectivity for the formation of multi-carbon products and the stability of the catalyst.
Smart Images

Figure CN121045567A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalysts, and more specifically, to copper-based metal-organic framework (MOF) electrocatalysts suitable for electrocatalytic CO2 reduction reaction (ECO2RR). Background Technology
[0002] Massive carbon dioxide emissions have led to severe global environmental problems such as the greenhouse effect, ocean acidification, and sea-level rise. As a rich source of carbon in the atmosphere, carbon dioxide could be converted into chemical feedstocks and energy through electrochemical reactions using renewable electricity, representing a promising strategy. However, electrocatalytic carbon dioxide reduction faces numerous challenges, including competition from hydrogen evolution reactions and the complexity of product formation due to the diverse reaction steps. Furthermore, compared to single-carbon (C1) products, multi-carbon (C2) products are more complex to generate. 2+ The selectivity for products (especially ethylene) remains low. Furthermore, both the surface properties of the catalyst and local environmental conditions affect the reaction pathway and activity of the electrocatalytic carbon dioxide reduction reaction. Copper is a unique catalyst of great interest in the electrocatalytic carbon dioxide reduction reaction because it can couple adsorbed *CO or *CHO intermediates to convert carbon dioxide into multi-carbon products and exhibits high Faradaic efficiency (FE). Current research has found that the activity and selectivity of copper-based catalysts in the electrocatalytic carbon dioxide reduction reaction for the formation of multi-carbon products can be improved through methods such as composition, morphology, defects, and surface modification. Therefore, the urgent need is to develop copper-based electrocatalytic carbon dioxide reduction catalysts with high energy efficiency, high Faradaic efficiency, and long-term stability to obtain multi-carbon products.
[0003] Metal-organic frameworks (MOFs), with their large specific surface area, customizable porous structures, and precisely controllable active sites and coordination microenvironments, hold considerable potential in the field of electrocatalytic carbon dioxide reduction (CO2 reduction). However, in most MOFs, the distance between their catalytic active sites typically hinders efficient coupling of carbon dioxide (CC), causing many original copper-based MOFs to tend to generate single-carbon products rather than multi-carbon products. One feasible solution is to design novel structures or create dual-copper active sites by doping MOFs. These sites, due to their suitable charge density, short Cu-Cu distance, and hydrogen bonding ability with surrounding ligands, can enhance the coverage of *CO intermediates and promote CC coupling reactions. Furthermore, in self-assembled MOFs, the relatively weak coordination bonds can weaken their stability as electrocatalysts. To address these issues, weaker bonds (such as Cu-O or Cu-N bonds) can be replaced with chemical bonds with stronger binding energies (such as Cu-S bonds) to ensure structural integrity at low reduction potentials. Furthermore, in terms of generating multi-carbon products, the unstable +1 valence copper (Cu(I)) exhibits higher activity and selectivity than the common metallic state (Cu(0)) and the +2 valence copper (Cu(II)).
[0004] Considering the above factors, certain azole molecules can be used as ligands to ensure that copper in the nitrogen-rich metal-organic framework structure remains stable in a highly active valence state during the electrocatalytic carbon dioxide reduction reaction. Furthermore, precise control of the coordination on the electrocatalyst surface is crucial for the activation of carbon dioxide and the stability of intermediates, directly affecting product selectivity. Additionally, studies have shown that insufficiently coordinated copper sites are particularly advantageous for the electroreduction of carbon dioxide to C2 hydrocarbons. Therefore, to achieve high selectivity for C2 products, suitable azole ligands must be selected when designing and synthesizing stable metal-organic framework structures. The metal-organic framework structure should include two copper sites, a stable Cu(I) valence state, and highly active unsaturated copper sites to serve as an electrocatalyst.
[0005] In summary, there is still a need in the field for a copper-based catalyst that can preferentially generate multi-carbon products (such as ethylene) rather than single-carbon products during the electrocatalytic reduction of carbon dioxide, and the present invention meets this need. Summary of the Invention
[0006] The purpose of this invention is to provide a compound, material, apparatus, or method to solve the above-mentioned technical problems.
[0007] According to a first aspect of the present invention, a copper-based metal-organic framework electrocatalyst for electrocatalytic carbon dioxide reduction is provided, comprising an orthogonal three-dimensional interconnected structure composed of a plurality of copper-5-mercapto-1-methyltetrazole (Cu-MMT) nanostructure monomers having interlayer spacing capable of capturing carbon dioxide molecules for electrocatalytic carbon dioxide reduction.
[0008] According to one embodiment of the present invention, the copper-5-mercapto-1-methyltetrazole nanostructure monomer is polymerized in orthogonal Pbca space groups to form a copper-based metal-organic framework.
[0009] According to another embodiment of the present invention, each copper-5-mercapto-1-methyltetrazole nanostructure monomer comprises six copper ions and six 5-mercapto-1-methyltetrazole ligands to form a three-dimensional cylindrical structure.
[0010] According to one embodiment of the present invention, each copper-5-mercapto-1-methyltetrazole nanostructure monomer has a single-atom copper point defect caused by unsaturated copper atoms.
[0011] According to one embodiment of the present invention, the single-atom copper point defect can cause the monomer structure to form multiple closely spaced double copper sites.
[0012] According to one embodiment of the present invention, the unsaturated copper atom coordinates with two sulfur atoms and one nitrogen atom from three symmetrically correlated 5-mercapto-1-methyltetrazole ligands to form an unsaturated Cu-1S-2N coordination structure.
[0013] According to one embodiment of the present invention, the unsaturated Cu-1S-2N coordination structure can provide catalytic carbon-carbon (CC) coupling to generate multi-carbon (C) bonds. 2+ The active site of the product.
[0014] According to one embodiment of the present invention, the copper-based electrocatalyst has a Faraday efficiency of 70-75% for multi-carbon products at -1.15V (relative to the reversible hydrogen electrode).
[0015] According to one embodiment of the present invention, the copper-based electrocatalyst has a Faraday efficiency of 50-55% for ethylene products at -1.15V (relative to the reversible hydrogen electrode).
[0016] According to a second aspect of the present invention, a method for preparing a copper-based metal-organic framework electrocatalyst is provided, comprising the following steps: A copper nanowire / isopropanol solution was added to a 5-mercapto-1-methyltetrazole / isopropanol solution and vortexed for at least 1 minute to obtain a mixture at a specific temperature. The mixture is placed in a container at a preset temperature and left to stand for a specified period of time; and Centrifuge the mixture to separate the copper-based metal-organic framework electrocatalyst.
[0017] According to one embodiment of the present invention, the concentration of the copper nanowire / isopropanol solution is 0.1-1 mg / mL; the concentration of the 5-mercapto-1-methyltetrazole / isopropanol solution is 0.5-6 mM; the specific temperature is room temperature; the preset temperature is 4-6 °C; the duration is 10-16 hours; and the copper-based metal-organic framework electrocatalyst is a rhombic metal-organic framework (copper-5-mercapto-1-methyltetrazole-1) with a thickness of about 200 nm.
[0018] According to another embodiment of the present invention, the concentration of the copper nanowire / isopropanol solution is 0.1-1 mg / mL; the concentration of the 5-mercapto-1-methyltetrazole / isopropanol solution is 0.5-6 mM; the specific temperature is room temperature; the preset temperature is 25°C; the duration is 36 hours; and the copper-based metal-organic framework electrocatalyst is a rhombic metal-organic framework (copper-5-mercapto-1-methyltetrazole-2) with a thickness of approximately 700 nm.
[0019] According to another embodiment of the present invention, the concentration of the copper nanowire / isopropanol solution is 0.1-1 mg / mL; the concentration of the 5-mercapto-1-methyltetrazole / isopropanol solution is 25 mM; the specific temperature is room temperature; the preset temperature is 0°C; the duration is 36 hours; and the copper-based metal-organic framework electrocatalyst is a paddle-shaped metal-organic framework (copper-5-mercapto-1-methyltetrazole-3).
[0020] According to one embodiment of the present invention, the concentration of the copper nanowire / isopropanol solution is 0.1-1 mg / mL; the concentration of the 5-mercapto-1-methyltetrazole / isopropanol solution is 50 mM; the specific temperature is room temperature; the preset temperature is 0°C; the duration is 24 hours; and the copper-based metal-organic framework electrocatalyst is a broom-shaped metal-organic framework (copper-5-mercapto-1-methyltetrazole-4).
[0021] According to one embodiment of the present invention, the total amount of 5-mercapto-1-methyltetrazole exceeds the total amount of copper nanowires to ensure that the copper nanowires can be completely reacted without residue.
[0022] According to a third aspect of the invention, an energy conversion device is provided. More specifically, the device comprises the aforementioned copper-based metal-organic framework electrocatalyst to convert carbon dioxide in air or exhaust gas into ethylene. Attached Figure Description
[0023] Referring to the accompanying drawings, embodiments of the present invention will be described in more detail below, wherein:
[0024] Figure 1A-1CA schematic diagram showing the structure of copper-5-mercapto-1-methyltetrazole nanoparticles is displayed. Figure 1A The synthesis process of the copper-5-mercapto-1-methyltetrazole nanostructure is shown. Figure 1B This reveals the spatial geometry of the copper-5-mercapto-1-methyltetrazole nanostructure. Figure 1C This shows the Cu-Cu distance between asymmetric units or adjacent units in the copper-5-mercapto-1-methyltetrazole nanostructure;
[0025] Figure 2A-2B The porous structure of the copper-5-mercapto-1-methyltetrazole metal-organic framework is shown, in which... Figure 2A It's a top view. Figure 2B It is a side view;
[0026] Figure 3A-3G The structural characterization of copper-5-mercapto-1-methyltetrazole-1 is shown, in which Figure 3A Comparison of powder X-ray diffraction pattern and simulated pattern of copper-5-mercapto-1-methyltetrazole-1. Figure 3B 3C is a scanning electron microscope image of copper-5-mercapto-1-methyltetrazole-1. Figure 3C For another scanning electron microscope image, Figure 3D This is a transmission electron microscope image of copper-5-mercapto-1-methyltetrazole-1. Figure 3E This is another transmission electron microscope image. Figure 3F Selected area electron diffraction (SED) images of copper-5-mercapto-1-methyltetrazole-1 are shown. Figure 3G The image shows a scanning electron microscope image and its corresponding elemental distribution map;
[0027] Figure 4A-4L Fine structural analysis of copper-5-mercapto-1-methyltetrazole-1 is shown, in which Figure 4A The Fourier transform infrared spectra of copper-5-mercapto-1-methyltetrazole-1, copper nanowires, and 5-mercapto-1-methyltetrazole are displayed. Figure 4B-4E The N1s spectra of high-resolution X-ray photoelectron spectroscopy for copper-5-mercapto-1-methyltetrazole-1 are shown below. Figure 4B S2p Figure 4C Cu2p Figure 4D ) and Cu LMM ( Figure 4E The map of ) Figure 4F For the standardized near-edge X-ray absorption spectrum of copper K-edge, Figure 4G Fourier transform of the k2-weighted extended X-ray absorption fine structure map. Figure 4H The fitting results of the copper K-edge extended X-ray absorption fine structure map of copper-5-mercapto-1-methyltetrazole-1, along with its R-space and inverse Fourier transform (inset). Figure 4I-4LCopper-5-mercapto-1-methyltetrazole-1 (…) were shown. Figure 4I ), copper sulfide ( Figure 4J ), copper phthalocyanine ( Figure 4K ) and standard copper foil ( Figure 4L ) of k 2 Wavelet transform of weighted copper K-edge extended X-ray absorption fine structure map;
[0028] Figure 5A-5L Fine structural characterization of copper-5-mercapto-1-methyltetrazole is shown, in which... Figures 5A-5C They are copper-5-mercapto-1-methyltetrazole-2 ( Figure 5A ), copper-5-mercapto-1-methyltetrazole-3 ( Figure 5B ) and copper-5-mercapto-1-methyltetrazole-4 ( Figure 5C Scanning electron microscope images of ) Figure 5D-5F They are copper-5-mercapto-1-methyltetrazole-2 ( Figure 5D ), copper-5-mercapto-1-methyltetrazole-3 ( Figure 5E ) and copper-5-mercapto-1-methyltetrazole-4 ( Figure 5F Transmission electron microscope images of ) Figure 5G A comparison of powder X-ray diffraction patterns and simulated patterns of three copper-5-mercapto-1-methyltetrazole samples (copper-5-mercapto-1-methyltetrazole-2-4) is presented. Figure 5H The Fourier transform infrared spectrum of the copper-5-mercapto-1-methyltetrazole sample is shown. Figure 5I High-resolution X-ray photoelectron spectroscopy of Cu LMM for copper-5-mercapto-1-methyltetrazole sample. Figure 5J High-resolution X-ray photoelectron spectroscopy of Cu 2p from copper-5-mercapto-1-methyltetrazole sample. Figure 5K Near-edge structure of copper K-edge X-ray absorption normalized to copper-5-mercapto-1-methyltetrazole sample. Figure 5L Sample k of copper-5-mercapto-1-methyltetrazole 2 Fourier transform of weighted extended X-ray absorption fine structure map;
[0029] Figures 6A-6B High-resolution X-ray photoelectron spectra of N1s and S2p of four copper-5-mercapto-1-methyltetrazole samples are shown. Figure 6A For N1s spectrum, Figure 6B S2p map;
[0030] Figures 7A-7C The spectrum comparison shows that of copper-5-mercapto-1-methyltetrazole-1-4, copper sulfide, and copper phthalocyanine is shown. Figure 7A For the standardized Cu K-edge X-ray absorption near-edge structure spectrum, Figure 7B A magnified view of the near-edge structure X-ray absorption spectrum of the normalized Cu K-edge. Figure 7C Fourier transform of the k2-weighted extended X-ray absorption fine structure map is shown;
[0031] Figures 8A-8D The average Faradaic efficiency of various reduction products of copper-5-mercapto-1-methyltetrazole samples at different potentials is shown, where copper-5-mercapto-1-methyltetrazole-1 ( Figure 8A ), copper-5-mercapto-1-methyltetrazole-2 ( Figure 8B ), copper-5-mercapto-1-methyltetrazole-3 ( Figure 8C ) and copper-5-mercapto-1-methyltetrazole-4 ( Figure 8D );
[0032] Figures 9A-9F The electrocatalytic performance of the copper-5-mercapto-1-methyltetrazole sample in the carbon dioxide reduction reaction is shown, among which... Figure 9A This shows the proportion of Faraday efficiency of multi-carbon products in the total product. Figure 9B This displays the Faradaic efficiency ratio of ethylene products in the total product. Figure 9C This displays the ratio of multiple carbons to single carbons in the total product. Figure 9D This indicates the ratio of multi-carbon to single-carbon components in the gaseous products. Figure 9E The partial current density of ethylene in four copper-5-mercapto-1-methyltetrazole samples at different potentials is shown. Figure 9F The catalytic stability of copper-5-mercapto-1-methyltetrazole-isopropanol was measured at -1.1V (relative to the reversible hydrogen electrode) for at least 12 hours.
[0033] Figure 10A-10D The results of the stability test are displayed, among which Figure 10A The powder X-ray diffraction patterns are shown before and after the stability test of copper-5-mercapto-1-methyltetrazole-isopropanol. Figure 10B and Figure 10C Both images show transmission electron microscopy (TEM) images of copper-5-mercapto-1-methyltetrazole-1 after a stability test at -1.1 V (relative to the reversible hydrogen electrode) for more than 10 hours. Figure 10D It shows its scanning electron microscope image; and
[0034] Figure 11A-11B High-resolution X-ray photoelectron spectra of Cu 2p and Cu LMM before and after the stability test of copper-5-mercapto-1-methyltetrazole-isopropanol are shown. Figure 11A High-resolution X-ray photoelectron spectroscopy of Cu 2p Figure 11B This is the high-resolution X-ray photoelectron spectrum of CuLMM. Detailed Implementation
[0035] In the following description, the apparatus, materials, and / or methods relating to the electrocatalytic carbon dioxide reduction reaction and related operations are listed as preferred embodiments. It will be apparent to those skilled in the art that modifications, including additions and / or substitutions, can be made without departing from the scope and spirit of the invention. Specific details may be omitted below to avoid obscuring the invention; however, this document is prepared to enable those skilled in the art to practice the techniques disclosed herein without excessive experimentation.
[0036] According to a first aspect of the invention, a copper-based metal-organic framework electrocatalyst for electrocatalyzing the reduction of carbon dioxide is provided. More particularly, the copper-based metal-organic framework electrocatalyst comprises a plurality of copper-5-mercapto-1-methyltetrazole (Cu-MMT) nanostructure monomers. These monomers exhibit a unique polymerization mode within the orthogonal Pbca space group to form a copper-based metal-organic framework. Each copper-5-mercapto-1-methyltetrazole nanostructure monomer comprises six copper ions and six 5-mercapto-1-methyltetrazole ligands to form a three-dimensional cylindrical structure. Notably, the copper-5-mercapto-1-methyltetrazole nanostructure monomers possess single-atom copper point defects, attributed to the presence of unsaturated copper atoms, thereby forming multiple closely spaced double copper sites. These unsaturated copper atoms coordinate with two sulfur atoms and one nitrogen atom from three symmetrically correlated 5-mercapto-1-methyltetrazole ligands to form an unsaturated Cu-1S-2N coordination structure, which provides the active sites required for catalyzing carbon-carbon coupling reactions, thereby generating multi-carbon products. This electrocatalyst exhibits a Faradaic efficiency of 70-75% for multi-carbon products and 50-55% for ethylene products at -1.15V (relative to the reversible hydrogen electrode).
[0037] According to a second aspect of the present invention, a method for preparing the above-described copper-based metal-organic framework electrocatalyst is provided. The method comprises several steps to ensure the formation of the desired metal-organic framework structure. First, an isopropanol solution containing copper nanowires (1 mg / mL) is added to an isopropanol solution containing 5-mercapto-1-methyltetrazole (5 mM); then, the mixture is vortexed at room temperature for at least 1 minute; next, the resulting mixture is placed in a space within a predetermined temperature range for a period of time; finally, the mixture is centrifuged to separate the copper-based metal-organic framework electrocatalyst.
[0038] In some embodiments, when the concentration of the copper nanowire / isopropanol solution is 0.1-1 mg / mL, the concentration of the 5-mercapto-1-methyltetrazole / isopropanol solution is 0.5-6 mM, and the reaction time is 10-16 hours, the resulting copper-based metal-organic framework electrocatalyst is a rhombic metal-organic framework with a thickness of approximately 200 nm. Different metal-organic framework structures can be obtained by changing the reaction time and temperature: for example, extending the reaction time to 36 hours at room temperature prepares a rhombic metal-organic framework with a thickness of approximately 700 nm; increasing the concentration of the 5-mercapto-1-methyltetrazole solution to 25 mM and reacting at 0 °C forms a paddle-shaped metal-organic framework; and adjusting the concentration of the 5-mercapto-1-methyltetrazole solution to 50 mM and reacting at the same 0 °C forms a broom-shaped metal-organic framework. These variations provide flexibility in adjusting the properties of the copper-based metal-organic framework electrocatalyst to suit specific applications.
[0039] It is worth noting that the total amount of 5-mercapto-1-methyltetrazole added exceeds the total amount of copper nanowires used to ensure that the copper nanowires can be completely reacted without residue.
[0040] According to a third aspect of the present invention, an energy conversion device is provided. Specifically, the device includes the aforementioned copper-based metal-organic framework electrocatalyst for converting carbon dioxide in air or exhaust gas into ethylene.
[0041] Example
[0042] Example 1: Synthesis and characteristics of a copper-based metal-organic framework electrocatalyst for electrocatalytic carbon dioxide reduction reaction.
[0043] A copper-based metal-organic framework electrocatalyst was synthesized in isopropanol using a 5-mercapto-1-methyltetrazole ligand and copper nanowires as the copper source. The reaction temperature, concentration, and time could be further adjusted (e.g.,...). Figure 1A(As shown). In short, the preparation process of the copper nanowire solution is as follows: Copper chloride dihydrate (CuCl2·2H2O) and glucose are dissolved in deionized water to form a clear blue solution (solution A); simultaneously, oleylamine and oleic acid are mixed in ethanol to form a colorless and transparent liquid (solution B); then, under strong magnetic stirring, solution A and deionized water are slowly added dropwise to solution B to form a uniform blue-green emulsion; next, the above mixture is sealed and heated in a water bath, and stirred at 50°C for 12 hours; when the mixture turns milky yellow, it is transferred to an autoclave and reacted at 110°C for 6 hours; after cooling to room temperature, the product is separated from the solution by centrifugation (10,000 rpm, 6 minutes), and washed 3 times with a hexane / ethanol (volume ratio 3:1) mixture, once with ethanol, and twice with isopropanol. Finally, the precipitated copper nanowires are dispersed in isopropanol (1 mg / mL) by gentle sonication to prepare a copper nanowire / isopropanol solution. Next, the prepared copper nanowire / isopropanol solution was added to a 5 mM 5-mercapto-1-methyltetrazole / isopropanol solution. After vigorous vortexing for 1 minute at room temperature, the mixture was immediately transferred to the refrigerator (approximately 5°C) and allowed to stand for 24 hours. Subsequently, the product was separated by centrifugation (6000 rpm, 5 minutes) and washed four times with isopropanol. Finally, the resulting precipitate (copper-5-mercapto-1-methyltetrazole-1) was dispersed in isopropanol (1 mg / mL) by gentle sonication. The resulting electrocatalyst (copper-5-mercapto-1-methyltetrazole-1) was a rhombic metal-organic framework with a thickness of approximately 200 nm.
[0044] It is worth noting that the metal-organic frameworks prepared by this method possess a novel structure never before seen, which is significantly different from the common structures synthesized in the past. Figure 1B This novel copper-5-mercapto-1-methyltetrazole metal-organic framework exhibits an orthorhombic Pbca space group. Each asymmetric unit contains six copper ions and six 5-mercapto-1-methyltetrazole ligands, forming a three-dimensional cylindrical structure. One unsaturated copper atom is coordinated with two sulfur atoms and one nitrogen atom from three symmetrically correlated 5-mercapto-1-methyltetrazole ligands. The Cu-N and Cu-S bonds provide structural stability, while the unsaturated three-coordinate structure provides highly active sites. Due to the unique coordination mode, although the copper sites in each cluster are independent of each other, staggered loops form in the central part of the cylinder, resulting in short copper-copper distances. ( Figure 1C ).
[0045] Furthermore, the adjacent active copper ions exhibit extremely short copper-copper distances. Numerous studies have also demonstrated that shorter copper-copper distances facilitate carbon-carbon coupling in carbon dioxide reduction reactions, leading to the formation of multi-carbon products. Notably, large-diameter cylindrical monomeric porous structures (approximately...) They will be arranged vertically to form a single-layer structure, and intersect each other perpendicularly to form a structure with a large interlayer spacing (approximately). ) three-dimensional interconnection structure ( Figure 2A-2B On the one hand, this optimized pore size facilitates efficient capture of carbon dioxide, ensuring sufficient raw materials for the carbon dioxide reduction reaction; on the other hand, the optimized interconnected network structure helps to more fully expose active sites for better reaction with carbon dioxide and various intermediates. Furthermore, the methyl group (-CH3) as a side chain not only acts as an electron-donating group, affecting the electron distribution of copper atoms and making them more reactive, but also faces one side of the interlayer structure, forming a substantial hydrophobic layer, which further facilitates the formation of the three-phase interface during the reaction.
[0046] like Figure 3A The powder X-ray diffraction pattern shows that the crystal structure of copper-5-mercapto-1-methyltetrazole-1 is highly consistent with the simulated structure, indicating that the synthesis was successfully completed. Furthermore, the positions of the diffraction peaks did not shift, and no peaks of metallic copper or other copper-based compounds were detected, further confirming the completeness of the reaction and the high purity and singleness of the product. Further analysis of the detailed morphology and structure of copper-5-mercapto-1-methyltetrazole-1 using low / high magnification scanning electron microscopy and transmission electron microscopy yielded the following results: Figure 3B-3E As shown, copper-5-mercapto-1-methyltetrazole-1 exhibits a rhombic microplate structure with a smooth surface and uniform size, an average side length of 1.6-2.8 μm, and a thickness of 185-210 nm. Selected area electron diffraction patterns of individual nanoplatelets show clear diffraction points and regularly arranged patterns, indicating that copper-5-mercapto-1-methyltetrazole-1 is a single crystal with high crystallinity. Figure 3F Furthermore, the elemental distribution map of energy-dispersive X-ray spectroscopy using scanning electron microscopy also showed the uniform distribution of copper, nitrogen, and sulfur elements in the copper-5-mercapto-1-methyltetrazole-1 nanostructure. Figure 3G ).
[0047] To examine the chemical structure and valence state of copper-5-mercapto-1-methyltetrazole-1, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and X-ray absorption fine structure spectroscopy were used for characterization. First, the chemical structures of the ligand and the copper-5-mercapto-1-methyltetrazole-1 sample were analyzed by Fourier transform infrared spectroscopy. Figure 4AIn the Fourier transform infrared spectrum of the copper-5-mercapto-1-methyltetrazole-1 sample, the HNC=S deformation vibration, NH deformation vibration, and CN stretching vibration were clearly observed, confirming the formation of copper-sulfur and copper-nitrogen coordination, and the tetrazolium ring in the sample was well preserved. Simultaneously, the high-resolution N1s X-ray photoelectron spectroscopy (XPS) spectrum... Figure 4B The peak at approximately 400.5 eV and the S2p spectrum ( Figure 4C The peak at approximately 162.6 eV in Cu 2p X-ray photoelectron spectroscopy also confirms the above results. For the valence state of nitrogen, high-resolution Cu 2p X-ray photoelectron spectroscopy (...) Figure 4D The peaks appearing at 932.7 eV (2p 3 / 2) and 952.5 eV (2p 1 / 2) in Cu are similar to those in Cu. + / Cu 0 State correlation; notably, no satellite peaks were observed, indicating the absence of Cu. 2+ This low Cu2p binding energy can be attributed to the strong covalent interactions between copper-copper, copper-nitrogen, and copper-sulfur ligand bonds. Further CuLMM Auger spectroscopy measurements of the copper valence state revealed a broad peak at a binding energy of 570.0 eV, further confirming that only Cu exists on the sample surface. + ( Figure 4E Furthermore, the above results show that Cu(I) in the copper-5-mercapto-1-methyltetrazole-1 sample is coordinated with the nitrogen and sulfur atoms in the 5-mercapto-1-methyltetrazole ligand. Simultaneously, elemental composition analysis using X-ray photoelectron spectroscopy and energy-dispersive X-ray spectroscopy based on scanning electron microscopy shows that the carbon:nitrogen:sulfur:copper ratio highly matches the standard structure within the error range.
[0048] The local coordination environment of the copper active site in copper-5-mercapto-1-methyltetrazole-1 was further investigated using XAFS spectroscopy. Figure 4F As shown, the near-edge X-ray absorption spectrum of copper K-edge in copper-5-mercapto-1-methyltetrazole-1 is similar to that of copper sulfide, indicating that the predominant valence state of copper in copper-5-mercapto-1-methyltetrazole-1 is +1. This result is consistent with the X-ray photoelectron spectroscopy results. By analyzing the k... 2 Fourier transform was performed on the weighted copper K-edge extended X-ray absorption fine structure pattern to analyze the atomic environment of the copper sites. Figure 4G and Figure 4H Among them, the main peak of copper-5-mercapto-1-methyltetrazole-1 is located between the standard samples copper phthalocyanine and copper sulfide, indicating that copper-nitrogen and copper-sulfur bonds exist simultaneously in the copper-5-mercapto-1-methyltetrazole-1 nanostructure; further analysis revealed that the main peak is closer to copper sulfide, corresponding to the structural mode of copper coordinated with two sulfur and one nitrogen.
[0049] The fitting results of the extended X-ray absorption fine structure map show that the first shell scattering pathways in these samples are copper-nitrogen and copper-sulfur, and the bond lengths of copper-nitrogen and copper-sulfur are respectively... and Slightly smaller than the bond lengths in the standard structure, it is noteworthy that the average coordination numbers of copper-nitrogen and copper-sulfur are approximately 0.7 and 1.7, respectively, which are also lower than 1 and 2 in the ideal structure. This suggests that there may be some copper site defects or unsaturated copper sites in copper-5-mercapto-1-methyltetrazole-1, and these defective sites may be more conducive to improving the electrocatalytic activity or selectivity of the carbon dioxide reduction reaction. In addition, an unconventional copper-copper bond exists in copper-5-mercapto-1-methyltetrazole-1, with a bond length of [missing information]. After comparison with various copper-based materials, it was found that this close copper-copper distance only appears in copper-based inorganic compounds or metallic copper. Furthermore, waveform transformation analysis of the fine structure spectrum of copper K-edge extended X-ray absorption (FREE) was performed. Figure 4I-4L The results showed that nitrogen and sulfur atoms participated in the coordination of copper in the copper-based metal-organic framework, and a small amount of copper-copper coordination also existed. Combined with previous X-ray diffraction, high-resolution scanning electron microscopy, and selected area electron diffraction analyses, it can be determined that the basic structure of the copper-5-mercapto-1-methyltetrazole metal-organic framework is stable and its chemical composition is relatively simple, ruling out the possibility of other substances being mixed in. Further analysis and simulations indicated that these unconventional, close-knit copper-copper bonds may originate from residual copper atoms in the porous structure of the copper-5-mercapto-1-methyltetrazole. Due to the low reaction concentration leading to low reaction kinetics, it is speculated that during the reaction, some copper ions are trapped in the porous structure of the copper-5-mercapto-1-methyltetrazole metal-organic framework, similar to solvent molecules typically remaining in the pores of metal-organic frameworks. A small amount of copper ions may also remain inside the tubular structure of the copper-5-mercapto-1-methyltetrazole. Due to size constraints, the inserted copper ions are close to the copper ions in the surrounding barrel structure, thus copper-copper coordination can be detected in extended X-ray absorption fine structure analysis. It should be added that these remaining copper ions are not uniformly distributed in each tubular pore, but rather belong to point defects, and do not affect the overall crystal structure of copper-5-mercapto-1-methyltetrazole-1. This is highly consistent with the other structural and compositional analysis results mentioned earlier.
[0050] It is worth noting that copper-based metal-organic framework electrocatalysts of different sizes or morphologies can be obtained by adjusting the preparation parameters. For example, a rhombic copper-5-mercapto-1-methyltetrazole metal-organic framework (copper-5-mercapto-1-methyltetrazole-2) with a thickness of 700 nm was prepared: First, a copper nanowire / isopropanol stock solution was added to a 5 mM 5-mercapto-1-methyltetrazole / isopropanol solution and vortexed vigorously at room temperature for 1 minute; then, the mixture was allowed to stand at 25 °C for 36 hours, and the product was separated from the solution by centrifugation (6000 rpm, 5 minutes) and washed four times with isopropanol; finally, the precipitate (copper-5-mercapto-1-methyltetrazole-2) was dispersed in isopropanol (1 mg / mL) by gentle sonication. 1 Preparation of paddle-shaped copper-5-mercapto-1-methyltetrazole metal-organic framework (copper-5-mercapto-1-methyltetrazole-3): Copper nanowire / isopropanol stock solution was added to a 25 mM 5-mercapto-1-methyltetrazole / isopropanol solution and vortexed vigorously at 0 °C for 1 minute; then, the mixture was immediately transferred to an ice-water bath (approximately 0 °C) and allowed to stand for 36 hours; the product was then separated by centrifugation and washed four times with isopropanol; finally, the precipitate (Cu-5-mercapto-1-methyltetrazole-3) was dispersed in isopropanol (1 mg / mL) by gentle sonication. 1 Preparation of broom-like copper-5-mercapto-1-methyltetrazole metal-organic framework (copper-5-mercapto-1-methyltetrazole-4): Copper nanowire / isopropanol stock solution was added to a 50 mM 5-mercapto-1-methyltetrazole / isopropanol solution and vortexed vigorously for 1 minute; then, the mixture was immediately transferred to an ice-water bath (approximately 0°C) and allowed to stand for 24 hours; the product was then separated by centrifugation and washed four times with isopropanol; the precipitate (copper-5-mercapto-1-methyltetrazole-4) was then dispersed in isopropanol (1 mg / mL) by gentle sonication. 1 The different morphologies of the aforementioned metal-organic frameworks can be examined in detail using scanning electron microscopy and transmission electron microscopy images. Figures 5A-5F When the reaction is carried out at the same low concentration of 5-mercapto-1-methyltetrazole (5 mM) as used in the preparation of copper-5-mercapto-1-methyltetrazole-1, if the reaction time is extended to 48 hours, the resulting product still retains the morphology of rhomboid microplates, but its size and thickness increase significantly (copper-5-mercapto-1-methyltetrazole-2, side length: 9.5-11 μm, thickness: 700 nm, such as...). Figure 5A and 5D (As shown). Given the high forward reaction kinetics and spontaneity of this reaction, further finer morphological control can be achieved by using a lower temperature to reduce the reaction rate, such as... Figure 5B and 5EAs shown, when the reaction temperature was lowered to 0℃ and the reaction concentration was increased to 25mM, the obtained copper-5-mercapto-1-methyltetrazole metal-organic framework exhibited a well-dispersed paddle-like morphology (copper-5-mercapto-1-methyltetrazole-3), with a length of approximately 1.3 μm, a width of approximately 470 nm, and a thickness of approximately 110 nm. However, when the ligand concentration was further increased to 50mM under these low-temperature conditions, the product transformed into a uniform bi-headed broom-like structure (copper-5-mercapto-1-methyltetrazole-4), which can be considered as dozens of small "paddle-shaped" nanosheets aggregated head-to-head. Figure 5C and 5F The sample is approximately 3.5 μm long, with a broom-like section approximately 1.6 μm wide and a thinner section of 0.5 μm in the middle. Furthermore, the elements copper, carbon, nitrogen, and sulfur are uniformly distributed in each sample.
[0051] like Figure 5G As shown, the powder X-ray diffraction patterns of all synthesized samples are highly consistent with the simulated patterns, confirming the novel structure and good crystallinity of the copper-5-mercapto-1-methyltetrazole sample. Among them, the Fourier transform infrared spectra of the three synthesized samples show characteristic peaks at the same positions as copper-5-mercapto-1-methyltetrazole-1, and no other peaks were detected. Figure 5H Further analysis of the N1s and S2p spectra of the four synthesized samples confirmed the formation of Cu-S and Cu-N bonds in these samples. Figure 6A and 6B Regarding the copper valence state of copper-5-mercapto-1-methyltetrazole, since only one peak of approximately 571.5 eV appears in the copper LMM spectrum, and no satellite peaks appear in the high-resolution copper 2p spectrum (only two peaks at approximately 932.6 eV (2p 3 / 2) and approximately 952.0 eV (2p 1 / 2)), it can be concluded that the Cu in these copper-5-mercapto-1-methyltetrazole samples is in the +1 valence state. This further proves that the binding of the 5-mercapto-1-methyltetrazole ligand can stabilize the low valence state of copper. Furthermore, it is noteworthy that compared to copper-5-mercapto-1-methyltetrazole-1 and copper-5-mercapto-1-methyltetrazole-2, the peak positions of copper-5-mercapto-1-methyltetrazole-3 and copper-5-mercapto-1-methyltetrazole-4 are slightly shifted to the left, indicating that the copper valence state in these two samples is slightly higher. Figure 5I and 5J ).pass Figure 6A and 6B The high-resolution S2p and N1s spectra further confirmed that the four synthesized samples exhibited the same coordination mode.
[0052] Figure 5K and Figure 7AThe X-ray absorption near-edge structure patterns of the four samples were close to those of copper sulfide, consistent with the Cu(I) oxidation state in copper-5-mercapto-1-methyltetrazole, which is consistent with the results of X-ray photoelectron spectroscopy analysis. Figure 7B As shown in the magnified partial image, the copper valence states in the synthesized sample generally follow a trend of copper sulfide < copper-5-mercapto-1-methyltetrazole-2 < copper-5-mercapto-1-methyltetrazole-1 < copper-5-mercapto-1-methyltetrazole-3 < copper-5-mercapto-1-methyltetrazole-4 < < copper oxide. Fourier transform results of the K2-weighted R-space copper K-edge extended X-ray absorption fine structure show that, in approximately... The main peak appears at this location, originating from Cu-N and Cu-S bonds. Figure 5I and Figure 7C Furthermore, the main peak is closer to copper sulfide, indicating that the Cu-S bonds in copper-5-mercapto-1-methyltetrazole occupy a higher proportion, which is consistent with its crystal structure. Notably, by comparing the results of these four synthetic samples, the average copper coordination of the rhombic sample is significantly higher in intensity and displacement than that of the paddle-shaped sample and its aggregates. Figure 7C Furthermore, copper K-edge fitting results and waveform transformations further confirmed that both nitrogen and sulfur participated in the coordination of copper. Figure 4H and Figure 4I In the fitted samples, the coordination numbers of Cu-N and Cu-S bonds were approximately 1 and 2, respectively, perfectly matching the structure within the error range. Furthermore, Cu-Cu bonds were detected in copper-5-mercapto-1-methyltetrazole-1 and copper-5-mercapto-1-methyltetrazole-2, further explaining the slightly lower valence state of copper and the larger average coordination radius in these two samples. This suggests that they will perform even better in the electrocatalytic carbon dioxide reduction reaction. These characteristic results indicate that copper-5-mercapto-1-methyltetrazole possesses a uniformly arranged structure, abundant low-valence and unsaturated copper sites, high porosity, and good stability. These advantages are beneficial for its application as a highly efficient electrocatalyst in the electrochemical carbon dioxide reduction reaction.
[0053] Example 2: Evaluation of the performance of copper-5-mercapto-1-methyltetrazole sample in electrocatalytic carbon dioxide reduction reaction.
[0054] To evaluate the electrochemical carbon dioxide reduction performance of the copper-5-mercapto-1-methyltetrazole catalyst, the glassy carbon electrode with the copper-5-mercapto-1-methyltetrazole catalyst was tested in a gas-tight H-type battery device. In this device, a platinum sheet was used as the counter electrode, a silver / silver chloride electrode was used as the reference electrode, and a 0.1M potassium bicarbonate solution was used as the electrolyte. In short, the copper-5-mercapto-1-methyltetrazole metal-organic framework was first centrifuged from the stock solution and carefully washed with isopropanol for use in preparing the working electrode. To prepare the catalyst ink, 200 μg of the washed copper-5-mercapto-1-methyltetrazole nanostructure (based on copper) was added to a mixture of 200 μL isopropanol and 5 μL Nafion solution (5 wt.%). The mixture was then sonicated in an ice-water bath for 20 minutes to obtain a uniformly dispersed catalyst ink. Next, 50 μL of the catalyst ink was drop-coated onto a glassy carbon electrode with a diameter of 8 mm. Finally, the resulting working electrode was dried at room temperature for 20 minutes and then stored in a vacuum oven.
[0055] The carbon dioxide reduction reaction experiments were conducted at reduction potentials ranging from -1.0 to -1.25 V (relative to the reversible hydrogen electrode). To assess the selectivity during the reaction, online gas chromatography and... 1 H nuclear magnetic resonance (H nuclear magnetic resonance) 1H NMR was used to monitor gaseous and liquid products, with detected gaseous products including ethylene, methane, carbon monoxide, and hydrogen, and liquid products including formic acid, ethanol, isopropanol, acetic acid, and acetaldehyde. In summary, all electrochemical measurements were performed in a three-electrode system using an Ivium-n-Stat electrochemical system. The catalyst was tested in a hermetically sealed two-chamber H-type cell separated by an ion-exchange membrane (Nafion 212), using a carbon dioxide-saturated 0.1M potassium bicarbonate aqueous solution as the electrolyte (typically, both the anode and cathode chambers were filled with 8 mL of electrolyte). A glassy carbon electrode with the catalyst, a silver / silver chloride electrode (filled with saturated potassium chloride solution), and a platinum sheet served as the working electrode, reference electrode, and counter electrode, respectively. All potentials were measured relative to the silver / silver chloride reference electrode with 85% iR compensation. Furthermore, the potentials were converted to the reversible hydrogen electrode using the following formula: E (relative to the reversible hydrogen electrode) = E (relative to the silver / silver chloride electrode) + 0.197 + 0.0591 × pH. None of the detected potentials were corrected for solution resistance. Prior to the electrocatalytic test, carbon dioxide gas (99.999% purity) was introduced into a 0.1M potassium bicarbonate aqueous solution in the cathode chamber for 30 minutes. During the test, carbon dioxide gas was continuously introduced into the cathode chamber electrolyte at a flow rate of 20 standard cubic centimeters per minute. The gas outlet of the cathode chamber was directly connected to an online gas chromatograph to directly analyze the gaseous products of the carbon dioxide reduction reaction. This chromatograph was also equipped with two flame ionization detectors and one thermal conductivity detector. After 1 hour of carbon dioxide electrolysis, the liquid products in the cathode electrolyte were collected and analyzed. 1 Analysis was performed using H NMR spectroscopy. The Faraday efficiency of the gaseous products was calculated using the following formula: Where P, V, and T represent pressure (1 atm), gas flow rate (30 mL·min), and gas velocity, respectively. -1 The values are 1H and 25°C. v, N, F, and I represent the volume fraction of the gaseous products, the number of electrons transferred in the electrochemical reaction, the Faraday constant, and the current, respectively. After electrolysis, the liquid products in the cathode chamber are collected and analyzed by 1H nuclear magnetic resonance spectroscopy. For example, in a typical NMR test, the mixed solution used includes 600 μL of electrolyte and 30 μL of dimethyl sulfoxide solution (0.035% by volume, dissolved in heavy water).
[0056] The average Faraday efficiency of each reduction product at different potentials is as follows: Figures 8A-8DAs shown, the overall efficiency of the carbon dioxide reduction reaction and the selectivity of each product exhibit similar trends with changes in electrolysis potential. Within the given potential range, the overall Faradaic efficiency of the carbon dioxide redox reaction is higher than that of the hydrogen evolution reaction. At -1.1V, the copper-5-mercapto-1-methyltetrazole-1 sample (relative to the reversible hydrogen electrode) reaches 89.20%, while the copper-5-mercapto-1-methyltetrazole-3 sample can even reach approximately 91.25% at the same potential, indicating that the copper-5-mercapto-1-methyltetrazole catalyst has higher selectivity for the electrocatalytic carbon dioxide reduction reaction than the reversible hydrogen electrode. Figure 9A As shown, for the Faradaic efficiency of high-value-added multi-carbon products, parallelogram-shaped microplates with a thickness of approximately 200 nm exhibit excellent performance over a wide voltage range, reaching a maximum Faradaic efficiency (multi-carbon) of 74.04% at -1.15 V (relative to the reversible hydrogen electrode). Among all products, ethylene is one of the most important target products and the focus of most research. Notably, the copper-5-mercapto-1-methyltetrazole-1 sample showed the best performance in ethylene formation (e.g., ...). Figure 9B As shown, the highest Faradaic efficiency (ethylene) is 52.83% (-1.15V relative to the reversible hydrogen electrode), which is among the highest values known in the art for various copper-based metal-organic framework catalysts. Furthermore, this can be further verified by analyzing the multi-carbon / single-carbon product ratio of the total products and gaseous products. Notably, copper-5-mercapto-1-methyltetrazole-1 exhibits the highest multi-carbon / single-carbon product ratio at -1.05V (relative to the reversible hydrogen electrode), reaching 6.47. Figure 9C Meanwhile, regarding the gaseous products, the ratio of two carbons (ethylene) to one carbon (carbon monoxide + methane) was as high as 7.52 times, significantly higher than the other three samples. Figure 9D Furthermore, copper-5-mercapto-1-methyltetrazole-1 also exhibited the highest partial current density in ethylene, reaching 7.82 mA·cm⁻¹ at -1.25 V (relative to the reversible hydrogen electrode). 2 ( Figure 9E ).
[0057] During continuous electrolysis at a potential of -1.15 V (relative to the reversible hydrogen electrode), the copper-5-mercapto-1-methyltetrazole-1 sample exhibited excellent stability in the carbon dioxide reduction reaction, maintaining a nearly constant Faradaic efficiency (ethylene) (approximately 50%) for over 12 hours. Figure 9F After electrolysis, no significant morphological changes were observed in the scanning electron microscope images of the copper-5-mercapto-1-methyltetrazole-1 sample, and no peaks of any copper-based inorganic substances (Cu(0), copper sulfide, or copper oxide, etc.) were detected in the X-ray diffraction pattern, indicating that it can maintain its structural integrity after electrochemical testing. Figure 10A-10DFurthermore, X-ray photoelectron spectroscopy analysis of copper revealed that, after stability testing, copper maintained a stable +1 valence state and exhibited high catalytic performance, further validating the stability of the metal-organic framework structure. Figure 11A-11B ).
[0058] In summary, this invention provides a simple room-temperature solvent reaction method for synthesizing unconventional copper-5-mercapto-1-methyltetrazole nanosheets without the use of any surfactants. Furthermore, by adjusting the reaction time, temperature, and concentration, four different sizes and morphologies of copper-5-mercapto-1-methyltetrazole nanostructures can be obtained. Notably, the obtained copper-5-mercapto-1-methyltetrazole nanosheets consist of structurally stable cylindrical monomer structures with an unsaturated Cu-1S-2N coordination mode. Some cylindrical monomers retain additional single-atom copper point defects, slightly influencing the structure and forming numerous closely spaced double copper sites. Moreover, continuous cyclic electrolysis analysis shows that the unconventional copper-5-mercapto-1-methyltetrazole nanosheets provided by this invention exhibit excellent catalytic durability. Based on its optimized electronic structure, the single-atom copper point defects on the unconventional copper-5-mercapto-1-methyltetrazole nanosheets help lower the energy barrier for ethylene formation, thereby enhancing the CC coupling tendency.
[0059] As used herein, the terms “approximately,” “substantially,” “essentially,” and “about” are used to describe and explain a small variation. When used in conjunction with an event or situation, the term can refer to the exact occurrence of the event or situation, or approximately the occurrence of the event or situation, and may also include the near-precise occurrence. For example, when used in conjunction with a numerical value, these terms can cover a range less than or equal to ±10% of that value, such as a range less than or equal to ±5%, ±4%, ±3%, ±2%, ±1%, ±0.5%, ±0.1%, or ±0.05%.
[0060] The above description is provided for the purpose of illustrating and describing the invention, and is not intended to be exhaustive or to limit the invention to the precise forms disclosed. Many modifications and variations will be apparent to those skilled in the art.
[0061] The above embodiments were chosen and described in order to best explain the principles of the invention and its practical application, thereby enabling other skilled in the art to understand the various embodiments of the invention and the various modifications suitable for the intended particular use.
Claims
1. A copper-based metal-organic framework electrocatalyst for electrocatalytic carbon dioxide reduction, characterized in that, include: Multiple copper-5-mercapto-1-methyltetrazole nanostructure monomers form an orthogonal three-dimensional interconnected structure with interlayer spacing capable of capturing carbon dioxide molecules for electrocatalytic carbon dioxide reduction.
2. The copper-based metal-organic framework electrocatalyst according to claim 1, wherein the plurality of copper-5-mercapto-1-methyltetrazole nanostructure monomers are polymerized in orthogonal Pbca space groups to form the copper-based metal-organic framework.
3. The copper-based metal-organic framework electrocatalyst according to claim 1, wherein each of the copper-5-mercapto-1-methyltetrazole nanostructure monomers comprises six copper ions and six 5-mercapto-1-methyltetrazole ligands to form a three-dimensional cylindrical structure.
4. The copper-based metal-organic framework electrocatalyst according to claim 3, wherein each of the copper-5-mercapto-1-methyltetrazole nanostructure monomers has a single-atom copper point defect caused by unsaturated copper atoms.
5. The copper-based metal-organic framework electrocatalyst according to claim 4, wherein the single-atom copper point defects can cause the formation of multiple closely spaced double copper sites in the copper-5-mercapto-1-methyltetrazole nanostructure monomer.
6. The copper-based metal-organic framework electrocatalyst according to claim 4, wherein the unsaturated copper atom is coordinated with two sulfur atoms and one nitrogen atom from three symmetrically correlated 5-mercapto-1-methyltetrazole ligands to form an unsaturated Cu-1S-2N coordination structure.
7. The copper-based metal-organic framework electrocatalyst according to claim 6, wherein the unsaturated Cu-1S-2N coordination structure provides active sites for catalyzing carbon-carbon (CC) coupling to generate multi-carbon (C2+) products.
8. The copper-based metal-organic framework electrocatalyst according to claim 7, wherein the copper-based electrocatalyst has a Faraday efficiency of 70-75% for the multi-carbon product at -1.15V (relative to the reversible hydrogen electrode).
9. The copper-based metal-organic framework electrocatalyst according to claim 8, wherein the copper-based electrocatalyst has a Faraday efficiency of 50-55% for ethylene products at -1.15V (relative to the reversible hydrogen electrode).
10. A method for preparing the copper-based metal-organic framework electrocatalyst according to claim 1, characterized in that, include: A copper nanowire / isopropanol solution was added to a 5-mercapto-1-methyltetrazole / isopropanol solution and vortexed for at least 1 minute to obtain a mixture at a specific temperature. The mixture is placed in a container at a preset temperature and left to stand for a certain period of time. as well as The mixture was centrifuged to separate the copper-based metal-organic framework electrocatalyst.
11. The method according to claim 10, wherein the concentration of the copper nanowire / isopropanol solution is 0.1-1 mg / mL, the concentration of the 5-mercapto-1-methyltetrazole / isopropanol solution is 0.5-6 mM, the specific temperature is room temperature, the preset temperature is 4-6 °C, and the duration is 10-16 hours.
12. The method according to claim 11, wherein the copper-based metal-organic framework electrocatalyst is a rhombic metal-organic framework with a thickness of 200 nm.
13. The method according to claim 10, wherein the concentration of the copper nanowire / isopropanol solution is 0.1-1 mg / mL, the concentration of the 5-mercapto-1-methyltetrazole / isopropanol solution is 0.5-6 mM, the specific temperature is room temperature, the preset temperature is 25°C, and the duration is 36 hours.
14. The method according to claim 13, wherein the copper-based metal-organic framework electrocatalyst is a rhombic metal-organic framework with a thickness of 700 nm.
15. The method according to claim 10, wherein the concentration of the copper nanowire / isopropanol solution is 0.1-1 mg / mL, the concentration of the 5-mercapto-1-methyltetrazole / isopropanol solution is 25 mM, the specific temperature is room temperature, the preset temperature is 0°C, and the duration is 36 hours.
16. The method according to claim 15, wherein the copper-based metal-organic framework electrocatalyst is a paddle-shaped metal-organic framework.
17. The method according to claim 10, wherein the concentration of the copper nanowire / isopropanol solution is 0.1-1 mg / mL, the concentration of the 5-mercapto-1-methyltetrazole / isopropanol solution is 50 mM, the specific temperature is room temperature, the preset temperature is 0°C, and the duration is 24 hours.
18. The method according to claim 17, wherein the copper-based metal-organic framework electrocatalyst is a broom-shaped metal-organic framework.
19. The method of claim 10, wherein the total amount of 5-mercapto-1-methyltetrazole exceeds the total amount of the copper nanowires to ensure that the copper nanowires can be completely reacted without residue.
20. An energy conversion device, characterized in that, include: According to claim 1, the copper-based metal-organic framework electrocatalyst, wherein the device converts carbon dioxide in air or exhaust gas into ethylene.
